Atropine Challenge Test in Screening the Organophosphorus Poisoning Cases with Atypical Presentation; a Brief Report - Shadnia, Shahin; Zamani, Nasim; Nikpour, Sara; Saffaei, Ali; Farnia, Mohammad Reza (Archives of Academic Emergency Medicine, 2019)
Introduction: Atropine is not recommended in organophosphorus (OPs) poisoning cases without any obvious clinical signs. This study aimed to evaluate the clinical utility of Atropine challenge test in screening OPs poisoning cases with atypical presentation. Methods: In this prospective cross sectional study, after primary supportive care, patients with atypical pretentions of OPs poisoning underwent Atropine challenge test (1 mg intravenously) and demographic parameters, clinical presentations, and serum level of cholinesterase enzyme were compared between cases with positive and negative test results. Results: 20 patients with the mean age of 47.60 ± 13.25 years were studied. The mean time since exposure and initial symptoms was 6.17 ± 2.99 hours. The most common clinical presentations were tachycardia (55%) and flushing (35%). The atropine challenge test was positive in 3 (15.00%) cases. The two groups were the same regarding gender distribution (p = 0.582), mean age (p = 0.957), clinical presentation (p > 0.05), and mean PR interval (p = 0.729). The level of cholinesterase was 220.00 ± 15.52 U/mL and 332.17 ± 143.99 U/mL in patients with positive and negative Atropine challenge test, respectively (p = 0.006). Conclusion: Patients with positive Atropine challenge test had a significantly lower level of serum cholinesterase and response to Atropine in their therapeutic management. Hence, Atropine challenge test could be considered as a useful clinical test in the setting of acute OPs poising.